Global prevalence of myopia in children using digital devices: a systematic review and meta-analysis - Nader Salari; Saba Molaeefar; Amir Abdolmaleki; Mahan Beiromvand; Masoud Bagheri; Shabnam Rasoulpoor; Masoud Mohammadi (BMC Pediatrics)
Abstract Background The global prevalence of myopia among children has considerably increased over the past few decades, affecting the children’s eye health and quality of life. According to the inconsistent reports of myopia among children, the purpose of this systematic review and meta-analysis study was to determine the global prevalence of myopia in children using digital devices. Methods Various databases (PubMed, ScienceDirect, Embase, Web of Science, Scopus, and Google Scholar) were searched systematically (No time limit until September 2023, last updated in May 2024) using keywords of “Myopia Prevalence”, “Children”, “TV”, “Computer”, “Video games”, and “Smartphone”. PRISMA guideline was also used for paper collection based on the Inclusion/Exclusion criteria. The quality of articles was determined based on the STROBE checklist. Data analysis, heterogeneity assessment, publication bias, and all factors influencing heterogeneity were executed using the CMA software (v.2). Results Initially, 828 articles were identified through database assessment. 563 and 133 papers were evaluated using primary and secondary assessments, respectively. Ultimately, 17 eligible articles were selected for meta-analysis following paper exclusion. In this era, the global prevalence of myopia among children using computer and video games was reported 28.8% (95%CI:21.1–38), using TV (TV watching) was 35.4% (95%CI:20.6–53.7), and smartphone usage was 31.4% (95%CI:13.5–57.3). Conclusion Myopia is now recognized as a critical global issue with a daily increasing rate. Technology, along with various digital devices, causes several issues in this era. It is suggested that the application of all digital screens and smart devices can potentially increase the risk of myopia among children. Thus, the reduction of these smart device applications in children can alleviate the potential risk of myopia. The results of this study can be a guide for health policymakers and a useful advertisement for society and families in paying attention to this problem in children, as well as increasing health interventions such as early screening and timely diagnosis for treatment. In this regard, it can be effective in both prevention and increasing the quality of life of children.